2021
DOI: 10.48084/etasr.4547
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Factors Affecting Road Traffic Accidents in North Cyprus

Abstract: Road traffic accidents are a global issue. North Cyprus exhibits a similar trend to the rest of the world. Urbanization and the increasing number of vehicles come along with the increase of road traffic accidents. The objectives of the current study are to draw attention to the issue of road traffic accidents and to identify which factors are the main causes of road traffic accidents in North Cyprus. This article follows a two-stage study to examine the causes of this critical issue. In the first stage, a surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…In [7], it was shown that if crossing maneuvers are carried out in an undesignated place, this has a greater impact on stream velocity. In [52], a video evaluation was carried out on two places on a split four-lane city street, where a median opening on one location allowed people to cross. This site's average speed was 7.7km/h slower than the other location, and it was also observed that friction on the sides of the road, such as parked automobiles and people waiting for buses or cars, can narrow the route and slow down the oncoming traffic.…”
Section: A Weightage Factors For Elements Of Side Frictionmentioning
confidence: 99%
See 2 more Smart Citations
“…In [7], it was shown that if crossing maneuvers are carried out in an undesignated place, this has a greater impact on stream velocity. In [52], a video evaluation was carried out on two places on a split four-lane city street, where a median opening on one location allowed people to cross. This site's average speed was 7.7km/h slower than the other location, and it was also observed that friction on the sides of the road, such as parked automobiles and people waiting for buses or cars, can narrow the route and slow down the oncoming traffic.…”
Section: A Weightage Factors For Elements Of Side Frictionmentioning
confidence: 99%
“…In [12], a speed forecasting model was developed showing a 0.35Km/h reduction in speed for each additional pedestrian on the road per minute. Studies [2,12,52] investigated and analyzed how side friction variables affect travel time and capacity in urban environments, based on data obtained from numerous metropolitan regions, by performing macroscopic and microscopic analyses. These studies examined how every variable on side friction, such as pedestrians, bicycles, and stopped and parked vehicles, affected traffic flow, taking into account the distinct effects of each component.…”
Section: B Speed Prediction Model For Stretches With Pedestrian Movementmentioning
confidence: 99%
See 1 more Smart Citation
“…The causative risks of RTAs can be broadly categorized as human, vehicle, and environmental factors [5,6]. Age, sex, education, medical conditions, and driving speed are key human-related factors, while environmental causes involve defective and narrow roads, poor lighting, lack of familiarity, and bad weather [1,[7][8][9][10]. Authors in [7,11] confirm that human errors comprise the major cause of RTAs.…”
Section: Introductionmentioning
confidence: 99%
“…On the study of road and environmental factors, Kurdin 10 analyzed the in uence of geometry and road environment on road accidents in Kecamatan Abeli; Liu 11 found that severe weather has a signi cant impact on the consequences of high-speed accidents. In addition, Angin and Ali 12 found that negligent driving and speeding are the main causes of road tra c accidents through a study of people, vehicle, road and the environment; Hauer 13 studied the relationship between average annual daily tra c volume, number of commercial lanes, and speed limits and the probability of tra c accidents; Hou 14 conducted a detailed inference analysis based on tra c characteristics, highway geometry, pavement conditions, and weather conditions to derive the main causal factors of highway vehicle crashes; Li and Liu 15 identi ed time of day, weather, number of patrol vehicles and surveillance, and age and attributes of the accident driver as some of the factors contributing to high speed tra c accidents; Tra c accidents are the result of a combination of factors, human, vehicle, road and the environment 16 . In this paper, a total of 29 basic pedestrian-vehicle tra c accident causative factors, including drunk driving and pedestrians crossing the tra c lane illegally, are also obtained from three categories: people, vehicle, road and environment.…”
Section: Introductionmentioning
confidence: 99%